Experimental simulation of downward molten material relocation by jet ablation of structures and fuel coolant interaction in a fast reactor. (May 2018) - Sudha, A. Jasmin; Kumaresan, M.; Anandan, J.; Murthy, S.S.; Malarvizhi, B.; Lydia, G.; Ponraju, D.; Nashine, B.K.; Selvaraj, P.
Abstract : In the remote chance of a core melt-down accident in a fast reactor, the molten corium from the fuel subassembly can come out in the form of a liquid jet due to the prevailing transient pressure. This high temperature jet is capable of causing local breaches on horizontal solid structures such as the grid plate with which they come into contact inside the main vessel. After penetration through the plates, the molten jet undergoes fragmentation in the bulk coolant available below the grid plate, in the lower plenum and settles on the core catcher. Experimental investigation of molten material relocation in the downward direction is carried out with a wood's metal jet impinging on a pair of solid wood's metal plates. The wood's metal alloy is heated electrically to about 300 °C inside the melt chamber and released through a nozzle to impinge on the dry plates mounted on rigid supports and allowed to pierce through the plates. The jet then gets quenched in bulk water contained in the experimental vessel. The trajectory of vertical jet impinging on the set of two parallel horizontal plates is captured using a high speed camera. Thermocouples are placed on the top and bottom surface of the plates to assess the temperature evolution. The breach area formed on the plates by the hot molten jet is assessed from the experiments. The initial pressure of the liquid jet is varied from 0 bar to 2 bar gauge pressure. The mass of the debris collected on the breached wood's metal target plates and the stainless steel collector plate gives evidence that the entire molten mass of jet does not reach the bottom collector plate but gets distributed on all the plates. The particle size distribution is obtained for the fragmented wood's metal debris settled on the collector plate. It is observed that the mass median diameter of the fragmented particles and porosity of the debris bed decreases as the jet release pressure is increased. An empirical correlation between the particle size represented by the mass median diameter and the initial pressure of the jet is obtained.